2023
DOI: 10.1002/oby.23654
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of weekday time‐restricted eating to improve metabolic health in breast cancer survivors with overweight/obesity

Abstract: Objective: This study aimed to evaluate the implementation of telephone-based delivery of weekday-only time-restricted eating (TRE), its preliminary efficacy for metabolic outcomes, and concurrent lifestyle changes.Methods: Twenty-two breast cancer survivors aged 60+ years with overweight/obesity completed an 8-week feasibility study of 12 to 8 PM weekday-only ad libitum TRE. The intervention was delivered by one registered dietitian call, twice-daily automated text messages asking about eating start and stop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…76 Some trials suggest a detrimental impact of intermittent fasting on lean or FFM, 16,26,29,30 and physical activity 12,21,29,30,69 but other trials have shown no concerning alterations in either physical activity 18,19,23,31,63,64 or body composition. [6][7][8]22,23,31,51,55,60,64,66,69,70,75,90 Very few trials have assessed the impact of these interventions on sleep, 12,29,59,62,73 cardiorespiratory fitness 11,17,63,66 and muscular strength 11,68,69 and more work is needed to understand the impact of intermittent fasting on these risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…76 Some trials suggest a detrimental impact of intermittent fasting on lean or FFM, 16,26,29,30 and physical activity 12,21,29,30,69 but other trials have shown no concerning alterations in either physical activity 18,19,23,31,63,64 or body composition. [6][7][8]22,23,31,51,55,60,64,66,69,70,75,90 Very few trials have assessed the impact of these interventions on sleep, 12,29,59,62,73 cardiorespiratory fitness 11,17,63,66 and muscular strength 11,68,69 and more work is needed to understand the impact of intermittent fasting on these risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,10,11,[13][14][15]19,25,26,29,65,66 With poor reporting on diet in many intermittent fasting trials, changes in dietary quality as a result of the intervention(s) are often left unas- window is similar to their baseline. 76 Some trials suggest a detrimental impact of intermittent fasting on lean or FFM, 16,26,29,30 and physical activity 12,21,29,30,69 but other trials have shown no concerning alterations in either physical activity 18,19,23,31,63,64 or body composition. [6][7][8]22,23,31,51,55,60,64,66,69,70,75,90 Very few trials have assessed the impact of these interventions on sleep, 12,29,59,62,73 c...…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations